Fyn-dependent regulation of energy expenditure and body weight is mediated by tyrosine phosphorylation of LKB1 - Yamada, Eijiro (2010)
Fyn null mice display reduced adiposity associated with increased fatty acid oxidation, energy expenditure and activation of the AMP-dependent protein kinase (AMPK) in skeletal muscle and adipose tissue. The acute pharmacological inhibition of Fyn kinase activity with SU6656 in wild type mice reproduces these metabolic effects and induced a specific reduction in fat mass with no change in lean mass. LKB1, the main upstream AMPK kinase (AMPKK) in peripheral tissues was redistributed from the nucleus into the cytoplasm of cells treated with SU6656 and in cells expressing a kinase-deficient but not a constitutively kinase active Fyn mutant. Moreover, Fyn kinase directly phosphorylated LKB1 on tyrosine 261 and 365 residues and mutations of these sites resulted in LKB1 export into the cytoplasm and increased AMPK phosphorylation. These data demonstrate a novel crosstalk between Fyn tyrosine kinase and the AMPK energy-sensing pathway through Fyn-dependent regulation of the AMPK upstream activator LKB1.